2004
DOI: 10.1111/j.1471-0528.2004.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐protein‐bound iron and free radical damage in fetuses with rhesus haemolytic disease: influence of intrauterine transfusions

Abstract: Objective To determine iron-induced free radical damage in fetal rhesus haemolytic disease (RHD) before and after repeated intrauterine red blood cell transfusions and its relation to hydrops fetalis. Design Prospective, observational study.Setting Department of Obstetrics, Leiden University Medical Centre, the Netherlands.Population Fifty anaemic fetuses, including 13 hydropic ones, 9 preterm and 12 term neonates and 8 female non-pregnant adults. Methods Venous blood plasma samples were collected from 50 fetu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Apoptotic manifestation of oxidized lipid epitopes on the surface of apoptotic cells has been identified as an important facilitator of phagocytosis. 13,29,30 This implies that antioxidants effective in inhibiting MDA oxidation may affect MDA externalization, and hence modulate the phagocytosis of apoptotic cells and the resolution of inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…Apoptotic manifestation of oxidized lipid epitopes on the surface of apoptotic cells has been identified as an important facilitator of phagocytosis. 13,29,30 This implies that antioxidants effective in inhibiting MDA oxidation may affect MDA externalization, and hence modulate the phagocytosis of apoptotic cells and the resolution of inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…We have found that lipid-peroxidation of CECs generates MDA adducts that bind annexin V in an iron-dependent manner. Among these, apoptotic manifestation of oxidized lipid epitopes on the surface of apoptotic cells has been identified as an important facilitator of phagocytosis (Krajcovicova-Kudlackova et al 2004;Luykx et al 2004;Shetty et al 2002). This implies that anti-oxidants effective in inhibiting MDA oxidation may affect MDA externalization and hence modulate the phagocytosis of apoptotic cells and the resolution of inflammation.…”
Section: Oxidative Stress and Lipid-peroxidationmentioning
confidence: 96%
“…In a previous study we found no difference between the pretransfusion plasma MDA concentrations of subsequent transfusions [7], because the oxidative effect had probably disappeared after the 2-to 4-week interval between transfusions. Nevertheless, there is strong evidence that red blood cell transfusion induces lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In the RhD+ fetus, NPBI is already present before the first transfusion [7]. When small amounts of free hemoglobin from hemolyzed red blood cells enter the fetal circulation during intrauterine transfusion, this may deteriorate fetal antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%